1993
DOI: 10.1021/bi00073a003
|View full text |Cite
|
Sign up to set email alerts
|

Three ryanodine receptor isoforms exist in avian striated muscles

Abstract: Two isoforms of the ryanodine receptor (termed alpha and beta) are coexpressed in avian fast twitch skeletal muscle, whereas a single isoform is expressed in avian cardiac muscle. We have investigated the relationship between these three proteins, comparing several different properties. First, the three receptor isoform subunits have different mobilities on SDS-polyacrylamide gels. Second, monoclonal antibodies against the chicken skeletal muscle receptor isoforms recognize shared and unique epitopes in each r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 28 publications
1
31
0
Order By: Relevance
“…In contrast to mammalian skeletal muscle, which expresses predominantly RyR1 and only small amounts of RyR3 (Takeshima et al 1994(Takeshima et al , 1995, nonmammalian vertebrate skeletal muscle tissue was found to express both isoforms together at equal amounts ( Fig. 1; Airey et al, 1990Airey et al, , 1993Olivares et al, 1991;Lai et al, 1992;O'Brien et al, 1993). This finding has been interpreted both as a phylogenetic specialization using a 2-component model of Ca 2+ release in skeletal muscle (O'Brien et al, 1995) and as a phylogenetic precursor form of the mammalian muscle types (Ottini et al, 1996).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In contrast to mammalian skeletal muscle, which expresses predominantly RyR1 and only small amounts of RyR3 (Takeshima et al 1994(Takeshima et al , 1995, nonmammalian vertebrate skeletal muscle tissue was found to express both isoforms together at equal amounts ( Fig. 1; Airey et al, 1990Airey et al, , 1993Olivares et al, 1991;Lai et al, 1992;O'Brien et al, 1993). This finding has been interpreted both as a phylogenetic specialization using a 2-component model of Ca 2+ release in skeletal muscle (O'Brien et al, 1995) and as a phylogenetic precursor form of the mammalian muscle types (Ottini et al, 1996).…”
Section: Discussionmentioning
confidence: 97%
“…Two types of functionally distinguishable RyRs were found, as in other teleosts (Block et al, 1994;O'Brien et al, 1995) and sauropsids O'Brien et al, 1995;Ottini et al, 1996). Ottini et al, 1996 could show that the homologues of the two isoforms in chicken, termed ␣ and ␤ isoform and identified based on biochemical and immunochemical properties (Airey et al, 1990(Airey et al, , 1993Olivares et al, 1991;Lai et al, 1992;O'Brien, Meissner & Block, 1993), are mammalian RyR1 and RyR3. In contrast to mammalian skeletal muscle, which expresses predominantly RyR1 and only small amounts of RyR3 (Takeshima et al 1994(Takeshima et al , 1995, nonmammalian vertebrate skeletal muscle tissue was found to express both isoforms together at equal amounts ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This antibody has been shown to bind selectively to a variety of avian and mammalian RyR isoforms. 19 The reactivity of mAb110E for guinea pig RyR isoforms was determined by Western blotting. Homogenates of guinea pig aorta, ileum, cardiac muscle, and psoas muscle were size-fractionated by SDS-PAGE on 7.5% gels and transferred to PVDF membranes.…”
Section: Anti-ryr Antibodiesmentioning
confidence: 99%
“…Protein was determined according to Bradford [12]. Standard procedures were followed for SDS-PAGE gels and Western blot analysis of membrane fractions [13], using 2G6 anti-ryanodine-receptor antibody [14] kindly provided by Drs. J. Airey and J. Sutko.…”
Section: Isolation Of Membrane Fractionsmentioning
confidence: 99%